Anti-Inflammatory Effects of Polyherbal Formulation DKP on Acute Lung Injury Induced by Carrageenan in Rats - Phuong Thanh, Mai; Hong Ngoc, Tran Thi; Huong, Nguyen Thuc Thu; Thu, Nguyen Le Anh; Nguyen Thuy Dung, Vo; Minh, Phan Hong (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2026)
Abstract: DKP is a blend of various medicinal herbs known for their positive effects on respiratory ailments. This research aimed to assess the protective properties of DKP in a carrageenan-induced acute lung injury (ALI) model using Wistar rats. The rats received DKP orally once daily for 10 consecutive days as pretreatment. On the 10th day, lung injury was triggered by the intratracheal administration of 100 μl of a 2% carrageenan solution. Following 24 hours post-induction of the model, the rats were anesthetized, and samples were collected for further analysis. The findings indicated that pretreatment with DKP was associated with a tendency to reduce lung edema and decrease the levels of pro-inflammatory cytokines IL-1β and TNF-α in both bronchoalveolar lavage fluid and serum. Antioxidant measurements revealed that in the groups pretreated with DKP, the concentration of MDA showed a tendency to decline, while the GSH content tended to increase. Furthermore, pretreatment with DKP mitigated carrageenan-induced damage to lung tissue as observed through histopathological examination. Therefore, the DKP formulation demonstrated a potential protective effect against acute lung injury induced by carrageenan. Keywords: Acute lung injury (ALI), acute respiratory distress syndrome (ARDS), carrageenan, polyherbal, rat.